2015
DOI: 10.1063/1.4921651
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in (2-butoxyethanol + water) mixtures: Hydrophobicity-induced aggregation or criticality-driven concentration fluctuations?

Abstract: Micro-heterogeneity in aqueous solutions of 2-butoxyethanol (BE), a system with closed loop miscibility gap, has been explored via absorption and time-resolved fluorescence measurements of a dissolved dipolar solute, coumarin 153 (C153), in the water-rich region at various BE mole fractions (0 ≤ XBE ≤ 0.25) in the temperature range, 278 ≤ T/K ≤ 320. Evidences for both alcohol-induced H-bond strengthening and subsequent structural transition of H-bond network have been observed. Analyses of steady state and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…These values are approximately comparable to the rotational relaxation times of fluorescent probe molecules dissolved in aqueous 2BE solutions in the second concentration regime determined by using time-resolved fluorescence spectroscopic techniques13) . These findings obtained by the earlier studies support our assignment of relaxation modes 3 and 4.It is worth writing that the ε 2 value clearly exhibits the maximum at ca.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…These values are approximately comparable to the rotational relaxation times of fluorescent probe molecules dissolved in aqueous 2BE solutions in the second concentration regime determined by using time-resolved fluorescence spectroscopic techniques13) . These findings obtained by the earlier studies support our assignment of relaxation modes 3 and 4.It is worth writing that the ε 2 value clearly exhibits the maximum at ca.…”
supporting
confidence: 74%
“…Besides, many other studies were published so far, which examined aqueous 2BE systems using various kinds of techniques such as surface tensiometry 6) , calorimetry 7) , viscometry 8) , ultrasound relaxation 9) , dynamic light scattering 10,11) , Taylor dispersion measurement 12) , fluorescent spectroscopy 13) , molecular dynamics simulation 14) , X-ray scattering 15) , neutron scattering [16][17][18] , neutron spin echo 18) , and so on. In many studies listed above, most authors found maxima or inflection points in the measured physical quantities at certain 17 † Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy analysis was performed via the standard protocol described in earlier works. [68][69][70] Time resolved fluorescence anisotropy, ) t ( r was then constructed as follows:…”
Section: (Iii) Data Collection and Analysismentioning
confidence: 99%
“…This three dimensional tetrahedral H-bond network structure of water gets disrupted to two dimensional zig-zag chainlike structure at comparatively larger alcohol concentrations where the tetrahedral network of water can no longer accommodate alcohol molecules. 17,18,20 This effect is more pronounced while moving from small alcohols like ethanol (EtOH) to larger alcohols like tertiary butanol (TBA) because hydrophobic interaction plays a critical role in regulating the structural arrangement of both the specie in a given binary mixture. 18 Consequently, dynamical properties of aqueous solutions exhibit significant changes in presence of co-solvents.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Here, we explore whether the hydrophobic part containing four N-methyl groups of TMU acts in the similar manner in aqueous solutions as we had observed before in aqueous alcoholic solutions. [17][18][19][20] In this paper, we have investigated various compositions of TMU in water at different temperatures by UV-Visible absorption and fluorescence spectroscopic measurements. Steady state absorption and fluorescence emission of a nonreactive probe coumarin 153 (C153) in TMU/water binary mixtures have provided important information regarding the structural change in the three dimensional H-bonding network of water upon addition of TMU.…”
Section: Introductionmentioning
confidence: 99%